COMPONENT ANALYSIS OF VERBS RELATED TO MEDICAL DIAGNOSTICS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article examines the components of verbs used in the medical diagnostic process. Verbs play a crucial role in identifying pathologies in medical diagnostics. The article analyzes the lexical and grammatical features of verbs, as well as their adaptation to medical language. It also discusses in detail the role and significance of verbs in medical diagnostics and their semantic aspects.